Glass/epoxy fiber orientation effects on translaminar fracture toughness under Mixed mode(I/II) load using FPB specimen (Fracture and Structural Integrity, 2020)
To study glass/epoxy fiber orientation effects on translaminar fracture toughness under Mixed mode(I/II) load using asymmetric Four Point Bend specimen. Fracture toughness values for different fiber-oriented glass/epoxy laminates under Mixed modes are compared with unidirectional glass/epoxy laminates. Specimens were fabricated using hand layup technique with (0/45)° and (0/90)° fiber oriented glass fiber. The experimental study was conducted for 6 crack positions varying from 0 to 1 with an increment of 0.2 for Four Point Bend specimen. The specimens were tested under universal testing machine to obtain peak loads and further evaluate fracture toughness. The experimental test results show fracture toughness can be increased by orienting the fiber in the laminate. Fracture toughness is highly dominating for (0/90)° fiber-oriented laminates compared to 0° and (0/45)° glass/epoxy laminates.
Keywords: Asymmetric Four Point Bend; Stress Intensity Factor; Mixed mode I/II